Optical properties of germanium nanoparticles synthesized by pulsed laser ablation in acetone - Vadavalli, Saikiran; Valligatla, Sreeramulu; Neelamraju, Bharati; Dar, Mudasir H.; Chiasera, Alessandro; Ferrari, Maurizio; Desai, Narayana Rao (Frontiers in Physics, 2014)
Germanium (Ge) nanoparticles (NPs) are synthesized by means of pulsed laser ablation of bulk germanium target immersed in acetone with ns laser pulses at different pulse energies. The fabricated NPs are characterized by employing different techniques such as UV-visible absorption spectroscopy, photoluminescence, micro-Raman spectroscopy, transmission electron microscopy (TEM) and field emission scanning electron microscopy (FESEM). The mean size of the Ge NPs is found to vary from few nm to 40 nm with the increase in laser pulse energy. Shift in the position of the absorption spectra is observed and also the photoluminescence peak shift is observed due to quantum confinement effects. High resolution TEM combined with micro-Raman spectroscopy confirms the crystalline nature of the generated germanium nanoparticles. The formation of various sizes of germanium NPs at different laser pulse energies is evident from the asymmetry in the Raman spectra and the shift in its peak position towards the lower wavenumber side. The FESEM micrographs confirm the formation of germanium micro/nanostructures at the laser ablated position of the bulk germanium. In particular, the measured NP sizes from the micro-Raman phonon quantum confinement model are found in good agreement with TEM measurements of Ge NPs.